Innovations and Opportunities in Care for Black Mothers and Birthing People. Issue 2 (April 2023) - Syed, Gullnar; Sims, Jacqueline; House, Sherrell Hicklen; Bruno, Beverly; Boulware, Angel; Tang, Kylie; Curenton, Stephanie M.
Abstract : In recent years, there has been increased attention given to how racism fuels health inequities, including the inadequacy of prenatal care (PNC) that Black women and Black birthing people receive. This increase of attention has brought notable advancements in research, practice, and policy that intend to better understand and address these systemic inequities within the health care system. This review aims to provide an overview of promising developments in the study of Black mothers' and birthing people's experiences in PNC and delivery, to detail current research surrounding interventions to improve quality and mitigate bias in obstetric care, and to offer ways in which legislation can support such strategies targeting the root causes of inequities in care.